Does enhancing personal care assistants' own oral health influence their attitudes and practices towards oral care for residents – a pilot study. Issue 4 (17th May 2016) - Knevel, RJM; Foley, J; Gussy, M; Karimi, L
Abstract: Objectives: To investigate whether, within a residential care facility, increasing personal care assistants' (PCAs) awareness of their own oral health status and self‐care skills would alter existing attitudes and behavioural intentions related to the oral health care of residents. Methods: PCAs ( n = 15) in the dementia care unit of a residential care facility in Melbourne, Australia, were invited to participate in a small research project that appeared to test the effectiveness of a work‐place oral health educational programme in enhancing their own oral health whilst masking the actual outcome of interest, namely its effect on PCAs oral healthcare attitudes and practices towards the residents. Results: Post‐intervention, the self‐reported confidence of the PCAs to identify their personal risk for oral health problems, identifying common oral health conditions and determining the factors contributing to their personal oral health was increased significantly ( P < 0.05). Post‐intervention, the self‐reported confidence of the PCAs to feeling confident to identify factors that could contribute to poor oral health of residents, identify resident's higher risk for poor oral health and feeling confident in identifying common oral health conditions in residents was also increased significantly ( P < 0.05). Conclusion: The results of this pilot study show that the educational intervention to increase the personal care assistants' (PCAs) awareness of their own oral health status and self‐care skills increased the confidence of the carers to identify oral health risks in the residents, as well as increasing their self‐reported confidence in providing oral care to residents.